2012 IEEE Symposium on Computational Intelligence in Bioinformatics and Computational Biology (CIBCB) 2012
DOI: 10.1109/cibcb.2012.6217218
|View full text |Cite
|
Sign up to set email alerts
|

Data mining techniques for AFM- based tumor classification

Abstract: The present paper deals with the application of atomic force microscopy (AFM) as a tool for morphological characterization of histological brain tumor samples. Data mining techniques will be applied for automatic identification of brain tumor tissues based on AFM images by means of classifying grade II and IV tumors. The rapid advancement of AFM in recent years turned it into a valuable and useful tool to determine the topography of surface nanoscale structures with high precision. Therefore, it is used in a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…When using Euler-characteristics directly for classification, for each sample 256 features would need to be considered (i.e., the characteristic's values at 256 gray levels), which gives an unfavorable sample size to dimensionality ratio. However, even if [51] reported that it is possible to derive discriminative models directly out of Euler-characteristics data in such a case, some feature processing shall be applied in order to reduce the dataset's dimensionality. Since according to Figures 8 and 9 different Minkowski functionals (viz.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When using Euler-characteristics directly for classification, for each sample 256 features would need to be considered (i.e., the characteristic's values at 256 gray levels), which gives an unfavorable sample size to dimensionality ratio. However, even if [51] reported that it is possible to derive discriminative models directly out of Euler-characteristics data in such a case, some feature processing shall be applied in order to reduce the dataset's dimensionality. Since according to Figures 8 and 9 different Minkowski functionals (viz.…”
Section: Discussionmentioning
confidence: 99%
“…Euler-characteristics and contour length) can be well represented as curves, an obvious step is to reduce the measurements at 256 gray levels to some significant metrics regarding their curves. In this way, [51] presented the usage of 15 distinct geometrical features that have a sufficient descriptive nature for characterizing the Minkowski functionals, such as absolute value and position of extremum points, position of the zero-crossing, steepness measures, or areas under the curves. In this way, a dataset with 113 samples each of 15 features has been obtained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Permite sintetizar programas de computador que solucionem problemas sem a necessidade de serem programados para tal. A partir da elaboração inicial de Koza [133], em pouco mais de 20 anos aárea se expandiu consideravelmente, abrangendo diferentes campos de aplicação, tais como Biotecnologia [105,198], Engenharia Elétrica [69,192] e Finanças [160,203], além de apresentar novas representações [31,152], entre as quais as mais conhecidas:…”
Section: Principais Conceitosunclassified